Urinary calcium and matrix Gla protein levels in the kidney stones: a case-control study - Ali, Zulfikar; Selanno, Fradelino Esau; Gunawan, I Putu Gde Fredy; Sulchan, Mohammad; Birowo, Ponco; Winarni, Tri Indah (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Kidney stones are a global issue with varying prevalence. The most common metabolic risk factor is hypercalciuria, a condition where excess calcium in the urine promotes stone formation. Matrix Gla protein (MGP) inhibits stone formation by preventing crystal growth. This study aimed to analyze the correlation between urinary calcium and MGP levels in kidney stone formation. METHODS A case-control study at Kardinah Hospital, Indonesia, included 64 patients with kidney stone and 64 healthy controls. Exclusion criteria included renal failure, stroke, kidney tumor, heart failure, and hemodialysis. Urinary calcium and MGP were measured using the 5’-nitro-5’-methyl-BAPTA method and enzyme-linked immunosorbent assay. Cut-off values were determined via receiver operating characteristic analysis. RESULTS Among 128 participants (mean age: 51.6), the optimal cut-off for urinary MGP was 1,405 ng/l (p = 0.00024) with 62.5% sensitivity and 72% specificity. Urinary calcium cut-off was 72.5 mg/24 hours with 81.3% sensitivity and 62.5% specificity. Higher urinary calcium and MGP levels were linked to kidney stones (OR: 7.22; 95% CI: 3.23–16.18 and OR: 4.26; 95% CI: 2.03–8.96, respectively). A significant association was found between urinary calcium and MGP (OR: 5.11; 95% CI: 2.31–11.29, p = 0.00006) that hypercalciuria and increased MGP levels are predictors of kidney stone formation. CONCLUSIONS Urinary calcium and MGP levels are associated with kidney stones. Elevated urinary calcium (>1,405 ng/l) increases MGP levels more than 5-fold. Depending on their levels, urinary calcium and MGP act as both promoters and inhibitors of stone formation.